Dieta de hemidactylus frenatus (sauria: gekkonidae) en un área urbana de la región Caribe colombiana - Díaz Pérez, Jorge A.; Davila Suárez, Juan A.; Alvarez García, Deivys M.; Sampedro Marín, Alcides C. (Instituto de Ecología, A.C., 2012)
The aim of this work was to study the diet of Hemidactylus frenatus in an urban area of Colombian Caribbean region. Twenty five specimens were captured on human edifications at the Sincelejo municipality (Sucre). After dissection and analysis of the stomach content, we identify 12 prey groups being Hemiptera the item with the highest importance value index (IVI = 152.7). The data shows a generalist and opportunistic feeding pattern, feeding mainly on arthropods.